Zinc sulphate administered by transdermal iontophoresis improves breaking strength of surgical wounds in skin of alloxan-induced diabetic rats - Cassettari, Lucas Langoni [UNESP]; Dias, Pedro Colli Rocha [UNESP]; Lucchesi, Amanda Natália [UNESP]; de Arruda, Maurício Ferraz; Spadella, César Tadeu [UNESP] (FapUNIFESP (SciELO), 2013)
Purpose: To investigate the effect of zinc sulphate administered by transdermal iontophoresis (TDI) on mechanical resistance of surgical wounds performed in the skin of diabetic rats. Methods: One hundred and sixty male Wistar rats weighing approximately 250g were submitted to an incision surgery at the anterior region of abdomen and randomly distributed into four experimental groups with 40 non-diabetic control animals (G1) and 40 untreated diabetic animals (G2), both without any treatment of incisions; 40 non-diabetic animals (G3) and 40 untreated diabetic animals (G4), both with incisions treated with zinc sulphate, administered for a period of four consecutive days after surgery, in sessions of ten minutes duration, using a continuous-current electrostimulator (Zn + TDI). Each experimental group was further divided into four subgroups with ten rats each to be evaluated on the 4th, 7th, 14th, and 21st day after surgery. In each period were analyzed clinical and laboratory from the animals, and measured the breaking strength and hydroxyproline content (OH-P) of the skin scars. RESULTS: Breaking strength (BS) was significantly reduced (p<0.05) in skin scars of untreated diabetic rats (G2) on the 7th, 14th, and 21st postoperative days when compared to non-diabetic control rats (G1). In contrast, BS in skin scars of non-diabetic and untreated diabetic rats (G3, G4) treated with Zn + TDI showed significant increase (p<0.05) in those periods when compared with their respective controls with untreated incisions. The OH-P content of the scars did not show statistically significant variation in all studied groups at four different times evaluated after surgery. Conclusions: Zinc sulphate administered by transdermal iontophoresis had beneficial effect on the mechanical resistance of scars produced in the skin of diabetic rats. This therapeutic may have potential to reduce the complications observed in surgical wounds of the skin in diabetic subjects, mainly in most vulnerable stages of incisions to dehiscences, leakages and infections.
Keywords: Alloxan; Diabetes mellitus; Iontophoresis; Rats; Wound healing; Zinc sulfate; glucose; glycosylated hemoglobin; hydroxyproline; insulin; zinc sulfate; animal experiment; animal model; controlled study; diabetes mellitus; electrode; iontophoresis; male; nonhuman; postoperative period; rat; skin scar; strength; surgical technique; surgical wound